An overview of potential cardioprotective benefits of xanthophylls in atherosclerosis: an evidence-based review - Yuting Su; Feng Chen; Jiehua Chen; Mingfu Wang (Food Science and Human Wellness)
Atherosclerosis, as the most prevalent form of cardiovascular disease, is characterized by oxidized lowdensity lipoprotein (ox-LDL) accumulation in the vascular wall, increased inflammation of the large arteries, dysfunction of the endothelial cells (ECs) and vascular smooth muscle cells (VSMCs), which may eventually lead to the formation of plaques. Xanthophylls, one of the main groups of carotenoids, have been proposed as preventive agents or adjunct therapies to prevent and slow the progression of atherosclerosis due to their cardioprotective properties. However, the underlying preventive mechanism of action of xanthophylls on the pathogenesis of atherosclerosis remains unclear, and clinical evidence of the effect of xanthophylls on atherosclerosis have not yet been summarized and critically reviewed. In this regard, we conducted a comprehensive literature search in four scientific databases (PubMed, Google Scholar, ScienceDirect and Web of Science) and carefully analyzed the existing evidence to provide meaningful insights on the association between xanthophylls and atherosclerosis from various aspects. Based on the evidence from in vitro and in vivo studies, we explored several potential mechanisms, including antioxidant effect, anti-inflammatory effect, regulation of lipid metabolism, and modulation of ECs and VSMCs dysfunction, and we found that a clear picture of regulatory pathways of xanthophylls on atherosclerosis prevention and treatment is still lacking. In addition, epidemiological studies suggested the possible relationship among high dietary intake of xanthophylls, high plasma/serum xanthophylls and a reduced risk of atherosclerosis. Direct evidence from interventional studies investigating the effect of xanthophylls on atherosclerosis is very sparse, whilst indirect clinical evidence was only limited to astaxanthin and lutein. Therefore, well-designed long-term randomized controlled trials (RCTs) are highly recommended for future studies to investigate the effective dose of different xanthophylls on atherosclerosis prevention and their possible ancillary effect in conjunction with drug therapies on different stages of atherosclerosis.